Exploring causal relationships between inflammatory cytokines and allergic rhinitis, chronic rhinosinusitis, and nasal polyps: a Mendelian randomization study - Li, Li; Zhang, Yuanding; Liu, Hong; Wang, Tianqi; Li, Junxin; Wang, Xin (Frontiers in Immunology, 2023)
Objectives: Previous research has suggested connections between specific inflammatory cytokines and nasal conditions, including Allergic Rhinitis (AR), Chronic Rhinosinusitis (CRS), and Nasal Polyps (NP). However, a lack of robust research establishing the causal underpinnings of them. This Mendelian Randomization (MR) study aims to evaluate the causal relationships between 41 inflammatory cytokines and the incidence of AR, CRS and NP, thus providing deeper insights into the pathogenesis of these three disorders.This study employed a two-sample MR design, harnessing genetic variations derived from publicly accessible genome-wide association studies (GWAS) datasets. AR data was Genetic variants of AR were sourced from a GWAS with 25,486 cases and 87,097 controls (identifier: ukb-b-7178). CRS data originated from a GWAS conducted on European individuals, encompassing 1,179 cases and 360,015 controls (identifier: ukb-d-J32). NP data werewas extracted from a GWAS summary involving 1,637 cases and 335,562 controls (identifier: ukb-a-541). The data for 41 inflammatory cytokines were obtained from an independent GWAS encompassing 8,293 healthy participants. Inverse variance weighted (IVW), MR Egger regression and Weighted median were used to evaluate the causalities of exposures and outcomes. Furthermore, aA range of sensitivity analyses were implemented to assess the robustness of the results.The results revealed significant associations between elevated circulating levels of MIP-1α (odds ratio,